Gambaran Hasil Pemeriksaan Aktivitas Enzim Alanine Aminotransferase (ALT) pada Serum Setelah Disimpan Selama 14 Hari: Overview of Alanine Aminotransferase (ALT) Enzyme Activity Assay Result in Serum After Storage for 14 Days - Putri Kurniasiwi; Roosmarinto Roosmarinto; Narendra Yoga Hendarta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Storage of serum at 4°C over three days causes a 10% decrease in the enzyme Alanine Aminotransferase (ALT) activity. However, several laboratories store remaining serum samples for one week or even one month after examination, which is not under Good Laboratory Practice (GLP). The serum storage is used to anticipate if there is an examination error. This study aims to describe the results of examining ALT enzyme activity in serum that was immediately checked and stored for 14 days. This type of research is descriptive quantitative using the Pretest-Posttest Design. The sample in this study was human blood serum, with a total sample of 10 patients. Data were analyzed descriptively for all data obtained and presented in tabular form. The average yield of ALT enzyme activity examination before storage and storage on day seven and day 14 was 50.7 U/L, 46.1 U/L, and 40.5 U/L. This study concluded that there was a decrease in the results of examining the activity of the ALT enzyme by 9% on the 7th day and 20% on the 14th day. Therefore, it is suggested that laboratory staff check the sample as soon as possible. If there is a need to repeat the analysis, verify the results or add laboratory tests, samples should be frozen to ensure stability.